2014
DOI: 10.3390/ijms151018084
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Monomeric GTP-Binding Proteins in Macroautophagy in Saccharomyces cerevisiae

Abstract: Autophagy is a cellular degradation process that sequesters components into a double-membrane structure called the autophagosome, which then fuses with the lysosome or vacuole for hydrolysis and recycling of building blocks. Bulk phase autophagy, also known as macroautophagy, controlled by specific Atg proteins, can be triggered by a variety of stresses, including starvation. Because autophagy relies extensively on membrane traffic to form the membranous structures, factors that control membrane traffic are es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 84 publications
1
7
0
Order By: Relevance
“…Previous work has elucidated roles for several monomeric GTP-binding proteins, 11 including some known to function in post-Golgi compartments, such as Ypt31-Ypt32 13 . In this study, we showed that 2 additional monomeric GTP-binding proteins that function in this area, Arl1 and Ypt6, also have roles in autophagy.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Previous work has elucidated roles for several monomeric GTP-binding proteins, 11 including some known to function in post-Golgi compartments, such as Ypt31-Ypt32 13 . In this study, we showed that 2 additional monomeric GTP-binding proteins that function in this area, Arl1 and Ypt6, also have roles in autophagy.…”
Section: Discussionsupporting
confidence: 50%
“…There is ample evidence, particularly in S. cerevisiae , that many membrane-traffic regulators, including several monomeric GTP-binding proteins are indispensable for autophagy 11 . Examples include the Rab protein family members Ypt1, Ypt31-Ypt32 and Ypt7, 12-14 and the Arf/Arl/Sar family members Arf1-Arf2 and Sar1 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…No systematic study has been undertaken of all the GTPase proteins in even a simple unicellular organism like S. cerevisiae, although it is clear several members of the Arf/Arl/Sar and Ypt/Rab families are required for construction of the autophagosome and for fusion of the autophagosome with the vacuole. 4,23,24 Members of the Rac/Rho/Cdc42 family, proteins generally viewed as regulators of cell polarity and cytoskeletal function, also appear to have signaling roles in autophagy. 25,26 Interestingly, RhoA along with its downstream effector, ROCK1 appears to mediate switching between autophagy and apoptosis via control of Beclin-1 (the ortholog of Atg6 in S. cerevisiae) levels in mammalian cells.…”
Section: Future Directionsmentioning
confidence: 99%
“…Finally, small GTPases of the Arf/Arl/Sar and Rab families are required for both construction of the autophagosome and fusion of the autophagosome with the lysosome (or vacuole in yeast) in a variation of their roles as membrane traffic regulators for the secretory pathway and endocytosis. [4][5][6][7] In this Commentary, we will describe our recent work documenting roles for 2 GTPases in macroautophagy, Arl1, a member of the Arf/ Arl/Sar family of small GTPases, and Ypt6, a member of the Rab family, in S. cerevisiae, 8 describe how these data fit into a larger understanding of the roles of membrane traffic in macroautophagy, then discuss future directions. We will focus primarily on what has been learned from studies in yeast, but note that this process is highly conserved across eukaryotes, including higher plants and animals.…”
Section: Introductionmentioning
confidence: 99%
“…Susan and Peter [5] tried to analyse the role of GTP-binding proteins in transport along the exocytic pathway. Moreover, Yang and Rosenwald [3] summarized the functions of the monomeric GTP-binding proteins in macroautophagy in Saccharomyces cerevisiae. For the role of GTP binding sites in membrane trafficking, there are many researchers focusing on this field.…”
Section: Introductionmentioning
confidence: 99%